Experience with Prophylactic Gentamicin During Penile Prosthesis Surgery: A Retrospective Comparison of Two Different Doses. Issue 9 (28th July 2017) - Xie, Donghua; Gheiler, Victor; Lopez, Isabel; Nehrenz, Guy M.; Klopukh, Boris; Bianco, Fernando; Perito, Paul; Gheiler, Edward
Abstract: Background: Gentamicin has been determined to be active against a wide range of bacterial infections and has been commonly used as a preoperative antibiotic for inflatable penile prosthesis (IPP) implantation. However, the best dosing regimen to produce the safest optimal prophylactic effect remains to be determined. Aim: To compare low- and high-dose gentamicin as prophylaxis during IPP implantation. Methods: We retrospectively analyzed two groups of patients who underwent IPP placement from April 14, 2012 through April 13, 2016. Group 1 was composed of 490 patients who underwent IPP placement from April 14, 2012 through April 13, 2014 and received a low dose of preoperative gentamicin at 80 mg every 8 hours for 1 day. Group 2 was composed of 407 patients who underwent IPP placement from April 14, 2014 through April 13, 2016 and received a single high dose of preoperative gentamicin at 5 mg/kg. We compared the infection rates of IPP and any gentamicin-related toxicities. The same surgeon performed all procedures. All patients received additional vancomycin 1 g before incision and at 12 hours postoperatively. Outcome: Demographic data and IPP infection rate were compared and potential toxicities from the higher dose of gentamicin were closely monitored. Results: There were no significant differences in mean age, mean body mass index, and mean interval for IPP placement and IPP infection between the two groups. No toxicity was seen with the higher gentamicin dose. Six cases in group 1 (five de novo cases and one redo case, infection rate = 1.22%) and three cases in group 2 (two de novo cases and one redo case, infection rate = 0.74%) were found to have IPP infection. The infection rate in group 2 appeared to be lower than that in group 1, although a significant statistical difference was not achieved ( P = .057). Clinical Implications: These findings would help guide urologists in choosing an optimal preoperative gentamicin dose for IPP surgery. Strengths and Limitations: This is the first study to report on the usage of high-dose preoperative gentamicin for IPP surgery but with limitations as a retrospective study. Conclusions: Although not achieving a statistical difference, there was a trend for patients receiving a higher dose of preoperative gentamicin to have a lower IPP infection rate. No toxicity was encountered from the 5-mg/kg gentamicin dose. We recommend following prophylactic high-dose gentamicin guidelines.